Pelatihan Dan Pendampingan Pembelajaran Dalam Meningkatkan Kualitas Proposal Penelitian Pada Mahasiswa Kesehatan - Indawati, Rachmah; Arief Wibowo; Dinana Izzatul Ulya; Tamara Nur Budiarti (STKIP Andi Matappa, 2024)
Background: Health is basic need of human life. Many health problems have not been solved. This requires collaboration and involves multi disciplines. One of sciences that forms public health is biostatistics. However, biostatistics is considered difficult by students. Besides that, knowledge about research is needed to solve health problems. The individual level, students write proposals late, proposals are not specific. In order to maximize students' abilities, they need to provide research concepts and data analysis. The aim of the service was provided training and learning mentoring to make research proposals. Methods: Activities are carried out for one semester. Target is seventh semester students. The activity provides training on research concepts and methodology. Results: Results show increased knowledge. This good knowledge is transferred into action (35 skripsi proposals). Conclusion: learning mentoring helps students master concepts and foster good attitudes and behavior towards the learning process